A study of the cost analysis of various oral antihypertensive drugs available in Indian market - Arya, Neelesh; Agrawal, Shweta; Agrawal, Mehul (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Hypertension is a serious global public health problem. It accounts for 10% of all deaths in India and is the leading non-communicable disease. Recent studies have shown that the prevalence of hypertension is 25% in urban and 10% in rural people in India. It exerts a substantial public health burden on cardiovascular health status and health care systems in India. Antihypertensive treatment effectively reduces hypertension related morbidity and mortality. The cost of medications has always been a barrier to effective treatment. The increasing prevalence of hypertension requires use of cost effective treatment for the effective management of the disease. Methods: Cost of a particular drug (cost per 10 tablets) in the same strength and dosage forms being manufactured by different companies was obtained from Current Index of Medical Specialties, Jan‑April 2019 and “Indian Drug Review” (IDR) September 2018. Difference between the maximum and minimum cost of the same drug manufactured by different pharmaceutical companies was calculated and percentage cost variation was calculated. Results: The prices of a total of 24 drugs (15 single and 9 combination preparations), available in 59 different formulations were analysed. These 62 formulations are manufactured by different pharmaceutical companies. Conclusions: The average percentage price variation of different brands of the same oral antihypertensive drug manufactured in India is very wide. The appraisal and management of marketing drugs should be directed toward maximizing the benefits of therapy and minimizing negative personal and economic consequences.